2012
DOI: 10.1589/jpts.24.1255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Use of Smartphones on Pain and Muscle Fatigue in the Upper Extremity

Abstract: Abstract.[Purpose] The purpose of this study was to investigate the effect of the use of smartphones on the upper extremity and determine whether there were differences in these changes between smartphone and computer use.[Subject] Forty healthy young adults (18 male, 25 female) took part in this study.[Methods] The pressure pain threshold measurement was assessed at the center of the upper trapezius of the dominant upper limb of the subjects. Electrodes were attached to the subjects in the two experiment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 19 publications
1
60
0
1
Order By: Relevance
“…Silva et al [36] stated that musculoskeletal complaints were more frequent in individuals with high prevalence of electronic devices, and also the pain in the cervical and thoracolumbar area increases when the duration of these devices' usage increased (>4 hours/day). In addition, studies indicated that use of the smartphone was associated with complaints of upper extremity and neck pain, and the long-term use of a touchscreen smartphone may also increase the risk of developing musculoskeletal symptoms such as chronic neck and shoulder pain [21,45]. In this study, it was found that 3/4 of the students with pain complaints use their smartphones for over 4 hours, the individuals who complained of pain had a longer duration of smartphone usage, but there was no statistically significant relationship between the percentage of smartphone use more/less than 4 hours and the presence/absence of pain complaints ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al [36] stated that musculoskeletal complaints were more frequent in individuals with high prevalence of electronic devices, and also the pain in the cervical and thoracolumbar area increases when the duration of these devices' usage increased (>4 hours/day). In addition, studies indicated that use of the smartphone was associated with complaints of upper extremity and neck pain, and the long-term use of a touchscreen smartphone may also increase the risk of developing musculoskeletal symptoms such as chronic neck and shoulder pain [21,45]. In this study, it was found that 3/4 of the students with pain complaints use their smartphones for over 4 hours, the individuals who complained of pain had a longer duration of smartphone usage, but there was no statistically significant relationship between the percentage of smartphone use more/less than 4 hours and the presence/absence of pain complaints ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that Physical problems with smartphone use have been attributed to the radiation from phones to change in posture to type and read, to the glare coming from a bright screen, and to constant wear and tear of wrist musculature. 11 Participants in the study reported various physical complaints noticed after smartphone use. Users, who reported physical problems, had sent significantly more messages on whatsapp during study duration.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the no logout option on whatsapp and the lack of a notification system on whatsapp which informs the users about a newly joined member, or newly changed profile picture or status. 11 Users who were aware about this and had tried to curb their smartphone use spent significantly less time on whatsapp, but exchanged comparable (non-significantly different) amount of messages and media on Whatsapp. Time spent on whatsapp correlated positively with time spent on web browsers.…”
Section: • Whatsapp Usage Statistics (Wus)mentioning
confidence: 99%
“…Several studies have investigated the impact of using smartphones on pain created in different parts of the body, and there is a correlation between the amount of time spent using a smartphone and the severity of the symptoms [3,5,6]. Not only that, other studies have shown that prolonged cell phones usage might lead to deficient postures, such as forward head posture and rounded shoulders [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing incidence of neck pain in different age groups [3]. Usually, neck pain increases as age increases, but nowadays younger patients are reporting neck pain more than ever [6]. Sustained pressure on the neck joints [10] is causing disturbed signals to the brain that might cause balance problems and disturbed neck proprioception [5,7,11].…”
Section: Introductionmentioning
confidence: 99%